Optimal timing of extracorporeal shock wave treatment to protect ischemic tissue - Reichenberger, Matthias; Keil, Holger; Müller, Wolf; Herold-Mende, Christel; Meirer, Romed; Gebhard, Martha Maria; Germann, Günter; Engel, Holger (Annals of plastic surgery, 2011)
Enhancement of flap survival through extracorporeal shock wave treatment (ESWT) is a promising new technique; however, no attempt has been made to define the optimal time point and frequency of ESWT to optimize treatment with ESWT for ischemic indications. Twenty-eight male Wistar rats were randomized into 4 groups and an oversized, random-pattern flap was raised and reattached in place in each animal. ESWT was applied 7 days before (group E7) or immediately after the surgical intervention (group E0). The third group was treated with ESWT 7 days before and additionally immediately after the operation (group E7/0). The fourth group served as a control group and did not receive any ESWT (group C). Seven days after flap harvest the results of flap survival, perfusion, microvessel density, and vascular endothelial growth factor concentrations were assessed. Flap survival was significantly increased in all ESWT groups as compared with the control group. The groups (E7 and E0) that received ESWT pre- or postoperatively showed a significant increase in flap perfusion and microvessel density. Combined pre- and postoperative ESWT application (group E0/E7) did not demonstrate a cumulative effect in any evaluation. In this study, we were be able to prove the effectiveness of ESWT in the protection of ischemic tissue flaps. This study suggests that single postoperative application is the most efficacious protocol for clinical applications of ESWT in the treatment of ischemic tissue.
Gesehen am 14.09.2022